2022
DOI: 10.15251/jor.2022.184.481
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristics of LaCrxAl1-xO3: DFT approach

Abstract: "The magnetic, electronic, and optical properties of Cr doped LaAlO3 are examined by Full Potential linearized augmented plane wave (FP-LAPW) method within Density functional theory (DFT). The pure compound (LaAlO3) is doped with different concentrations of chromium (Cr) to examine the doping effects on its characteristics. The calculations of band structure (BS) and density of states show Cr has major contribution while La, Al and O atoms have little involvement in the states near Fermi level. The magnetic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…[ 21 ] Javid et al observed the electromagnetic and optical features of Cr‐doped LaAlO 3 by density functional theory (DFT) approach and revealed that the system shows a semiconductor nature in both spin versions; it was also found that the resulting doped compound is suitable for spintronic and optoelectronic devices. [ 22 ] Zhang et al modeled thin films of La/Mn‐codoped STO in which FM was observed at room temperature because of magnetic coupling among free electrons and d ‐spins of Mn atom. [ 23 ] Furthermore, FM feature is also reported below 400 K in Mn‐doped STO [ 24 ] which exhibits complex magnetic ordering as it possesses magnetoelectric coupling.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] Javid et al observed the electromagnetic and optical features of Cr‐doped LaAlO 3 by density functional theory (DFT) approach and revealed that the system shows a semiconductor nature in both spin versions; it was also found that the resulting doped compound is suitable for spintronic and optoelectronic devices. [ 22 ] Zhang et al modeled thin films of La/Mn‐codoped STO in which FM was observed at room temperature because of magnetic coupling among free electrons and d ‐spins of Mn atom. [ 23 ] Furthermore, FM feature is also reported below 400 K in Mn‐doped STO [ 24 ] which exhibits complex magnetic ordering as it possesses magnetoelectric coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, HMF was first revealed while studying the SP of half-Heusler (NiMnSb) material [14]. Several TMs based perovskite materials such as Cr doped LaAlO 3 [15], V/Co-doped SrTiO 3 [16,17], iron-doped SrTiO 3 [18] and BaTiO 3 [19] etc. have been studied due to their HM features.…”
Section: Introductionmentioning
confidence: 99%